Lexicographic tools for describing substandard lexical systems of the contrasted languages - Tulegenova, М.К.; Zhunussova, Zh.N.; Khan, N.K.; Ayazbayeva, B.K. («Академик Е.А. Бөкетов атындағы Қарағанды ұлттық зерттеу университеті» КеАҚ баспасы, 2026)
The study explores challenges in describing non-standard lexical items within the lexicographic frameworks of different languages. The relevance of the study stems from the absence of a unified methodology for the description of non-standard vocabulary in modern lexicography. It is shown that the traditional lexicographic approaches often fail to reflect the full semantic, pragmatic, and sociolinguistic specificity of substandard lexemes. The paper justifies the need for a dedicated lexicographic instrument tailored to substandard vocabulary. An overview of current lexicographic strategies in both English and Russian traditions is presented using the examples of E. Partridge’s dictionary and S. Vakhitov’s Dictionary of Ufa Slang. Special focus is placed on microstructural elements of dictionary entries, including various types of grammatical, stylistic, and sociolinguistic annotations and the concept of the Lexicographic Method (LGM) as a basis for the semanticpragmatic analysis of substandard vocabulary. Drawing on the research findings, the authors advocate for a sociolexicographic approach aimed at developing a lexicographic portrait of a word. The resulting portrait integrates multiple linguistic dimensions such as phonetics, grammar, semantics, derivation, etymology, and contextual usage. The integration of these parameters makes it possible to adequately capture the linguistic and extralinguistic characteristics of substandard units. It is demonstrated that only an integral and systematized approach to lexicographic description allows for the accurate and context-sensitive representation of substandard vocabulary. The article proves that substandard lexicon, due to its dynamic, expressive, and socially marked nature, requires a distinct and more flexible lexicographic methodology. Thus, the article contributes to the development of contrastive and sociolexicographic theory by formulating a set of principles for dictionary compilation that meet the demands of both academic research and practical lexicography. The proposed approach offers a foundation for future lexicographic projects aimed at the comprehensive and culturally aware representation of non-standard language elements in bilingual and monolingual dictionaries. The results of the study can be applied in the design of specialized dictionaries and in broader linguistic research involving substandard varieties.
Қарама-қарсы тілдердегі бейәдеп лексикалық жүйелерді сипаттауға арналған лексикографиялық құралдар
Лексикографические средства для описания субстандартных лексических систем сопоставляемых языков
Keywords: substandard vocabulary; lexicographic method; microstructure; sociolexicography; semantisation